Pengaruh Shopping Lifestyle Dan Live Streaming Terhadap Impulse Buying Pada E-Commerce Tiktok Shop (Generasi Milenial Di Kabupaten Mamuju) - Maulidya, Maulidya; Dahri, Nur Wahyunianti; Sibgatullah, Muhammad (Pascasarjana Universitas Muhammadiyah Mamuju, 2026)
This study aims to analyze the influence of shopping lifestyle and live streaming on impulse buying among millennial users of TikTok Shop e-commerce in Mamuju Regency. This research employed a quantitative method with an associative approach. The population consisted of 288,382 people, and a sample of 100 respondents was determined using Slovin’s formula with purposive sampling, based on the criteria of millennial generation (aged 29–44 years) who are TikTok Shop users residing in Mamuju Regency. Data were collected through observation, interviews, documentation, and questionnaires. The data were analyzed using multiple linear regression, partial test (t-test), simultaneous test (F-test), and the coefficient of determination (R²). The results showed that shopping lifestyle had a significant partial effect on impulse buying (t-value 2.672 > t-table 1.985; sig. 0.009 < 0.05). Live streaming also had a significant partial effect on impulse buying (t-value 3.664 > t-table 1.985; sig. 0.000 < 0.05). Simultaneously, both shopping lifestyle and live streaming significantly affected impulse buying (F-value 23.194 > F-table 3.090; sig. 0.000 < 0.05), with a contribution of 32.4%. These findings indicate that although shopping lifestyle and live streaming play a role in shaping impulse buying behavior, their overall contribution is relatively low. Further research is strongly recommended to explore the remaining 67.6% of other factors that were not identified in this study but may influence impulse buying among millennial TikTok Shop users in Mamuju Regency.